Cryogenic modulation fast GC × GC–MS using a 10 m microbore column combination: Concept, method optimization, and application. Issue 5 (5th January 2018) - Giocastro, Barbara; Piparo, Marco; Tranchida, Peter Q.; Mondello, Luigi
Abstract: The present research is based on the concept of using a 10 m × 0.1 mm id column for cryogenic‐modulation fast comprehensive two‐dimensional gas chromatography with quadrupole mass spectrometry. Specifically, an 8.9 m × 0.1 mm id low‐polarity column was used as the first dimension, and a 1.1 m × 0.1 mm id medium‐polarity column was used as the second dimension. The main scope of the investigation was to develop a high peak‐capacity method, with an analysis time of approximately 10 min. Various aspects related to method optimization are discussed, as well as separation parameters such as peak capacity (in each dimension, and as a total value), first‐dimension sample capacity, peak widths, modulation ratio, sensitivity enhancement, and number of spectra per peak. The fast approach was evaluated in applications involving a mixture of cosmetic allergens and a sample of perfume. The approach proposed enables high‐resolution separations in a short time (across the C8 –C23 alkane range), as well as a considerable reduction of the consumption of gases for modulation cooling and heating.